Motivasi dan Supervisi Berhubungan dengan Kinerja Infection Prevention and Control Link Nurse (IPCLN) dalam Menerapkan Pencegahan dan Pengendalian Infeksi - Afriani Afriani; Mudatsir Mudatsir; Suryane Sulistiana Susanti (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2021)
This study aims to determine the relationship between motivation and supervision with the performance of nurses in implementing infection prevention and control in hospitals in Aceh Province. The research method used was a cross-sectional study. The results showed that motivation and supervision were significantly related to the performance of Infection Prevention and Control Nurses in Banda Aceh City Hospital and Kab. Aceh Besar (P-value < 0.05). In conclusion, the motivation variable, namely the need for achievement, is the most dominant predictor associated with the performance of Infection Prevention and Control Nurses at the Banda Aceh City Hospital and Kab. Aceh Besar. Keywords: IPCLN, Performance, Motivation, Nurse, Supervision